A national qualitative study of Hospital‐at‐Home implementation under the CMS Acute Hospital Care at Home waiver. Issue 1 (5th October 2022) - Gorbenko, Ksenia; Baim‐Lance, Abigail; Franzosa, Emily; Wurtz, Heather; Schiller, Gabrielle; Masse, Sybil; Ornstein, Katherine A.; Federman, Alex; Levine, David M.; DeCherrie, Linda V.; Leff, Bruce; Siu, Albert
Abstract: Background: The Centers for Medicare & Medicaid Services (CMS) announced the Acute Hospital Care at Home (AHCaH) waiver program in November 2020 to help expand hospital capacity to cope with the COVID‐19 pandemic. The AHCaH waived the 24/7 on‐site nursing requirement and enabled hospitals to obtain full hospital‐level diagnosis‐related group (DRG) reimbursement for providing Hospital‐at‐Home (HaH) care. This study sought to describe AHCaH implementation processes and strategies at the national level and identify challenges and facilitators to launching or adapting a HaH to meet waiver requirements. Methods: We conducted semi‐structured interviews to explore barriers and facilitators of HaH implementation. The analysis was informed by the Exploration, Preparation, Implementation, and Sustainment (EPIS) implementation framework. Interviews were audio recorded for transcription and thematic coding. Principal Findings: We interviewed a sample of clinical leaders ( N = 18; clinical/medical directors, operational and program managers) from 14 new and pre‐existing U.S. HaH programs diverse by size, urbanicity, and geography. Participants were enthusiastic about the AHCaH waiver. Participants described barriers and facilitators at planning and implementation stages within three overarching themes influencing waiver program implementation: 1) institutional value and assets; 2) program components, such as electronic health records, vendors, pharmacy, and patient monitoring; and 3) patient enrollment, including eligibility and geographic limits. Conclusions: Implementation of AHCaH waiver is a complex process that requires building components in compliance with the requirements to extend the hospital into the home, in coordination with internal and external partners. The study identified barriers that potential adopters and proponents should consider alongside the strategies that some organizations have found useful. Clarity regarding the waiver's future may expedite HaH model dissemination and ensure longevity of this valuable model of care delivery. Abstract : See related Editorial by Brody et al . in this issue.